Pengekploitasian Tanah Ulayat Berbasis Sistem Ekonomi Kerakyatan Yang Berkeadilan Sosial Dan Berkesinambungan - Zulheri, Zulheri (Jurnal Hukum & Pembangunan, 2016)
This article aims to visualize a concept for an appropriate exploitation of tanah ulayat (lands traditionally owned by local community/LTOBLC). This concept would reform the use of LTOBLC to welfare the local society. To envision this idea, this research identified the problems that the lack of scheme for managing the LTOBLC and misconception the principle of social justice as mentioned at the fifth Sila of Pancasila has disabled the local community to come out from the long-term structured poverty since the Dutch colonialism until now. Therefore, this research offers a new scheme dealing with the use of LTOBLC that required resolving the problems mentioned above. This scheme could be embodied through a mutual symbiosis between the local community and the company. However, this dramatically step would change the existing management of LTOBLC from PIR to plasma. To achieve a workable concept of the use of LTBOLC, it is necessary to introduce a new scheme of exploitation based on the concept of social Justice and its sustainability. To realize such proposal, I would argue that revitalization I 00%. This work concludes that the appropriate concept on the use of LTBOLC is required to correct such deficiency mentioned above to promote a fair and sustainable exploitation of the LTBOLCfor a welfare local community.